Radiocarbon trends in the pampean region (Argentina). biases and Demographic patterns during the final late pleistocene and holocene - Martínez, Gustavo (2015)
This paper compiles a database of radiocarbon dates of archaeological sites that are currently available for the Pampean region. Based on the probability distribution of radiocarbon dates from this database, major temporal trends are defined, taphonomic and scientific biases are evaluated, and their implications for demography are suggested. Results indicate a continuous archaeological signal between ca. 14,500 and 100calBP. During the final Late Pleistocene and the Early Holocene, the archaeological signal is low in ca. 14,500-12,800calBP, and increases to a moderate and continuous signal in ca. 12,800-7500calBP. The archaeological signal for the former lapse correspond to the early peopling of the region and is related to the inhabiting and exploitation of key landforms (e.g., rock shelters, river valleys) and critical resources (e.g., lithic raw material, water). The low amount of available dates for the Middle Holocene (ca. 7400-3700calBP), and the associated archaeological signal would be due to the combination of various factors such as taphonomic biases, organization of prehistoric populations, and even a possible low population density. The obtained low but continuous signal for this period are discussed in the framework of the proposed models for the human occupation of the region suggesting that a hypothesis about population extinctions and disruptions processes could not be sustained. Finally, during the Late Holocene (from 3700 to 100calBP) human occupations are recorded in all the micro-regions. Regardless of biases, this signal is interpreted as an increase in demographic density at a regional level.